Follistatin-like 1 suppresses sensory afferent transmission by activating Na+,K+-ATPase - Li, Kai-Cheng; Zhang, Fang-Xiong; Li, Chang-Lin; Wang, Feng; Yu, Ming-Yan; Zhong, Yan-Qing; Zhang, Kai-Hua; Lu, Ying-Jin; Wang, Qiong; Ma, Xiao-Li; Yao, Jun-Ru; Wang, Jin-Yuan; et al. (Neuron, 2011)
Excitatory synaptic transmission is modulated by inhibitory neurotransmitters and neuromodulators. We found that the synaptic transmission of somatic sensory afferents can be rapidly regulated by a presynaptically secreted protein, follistatin-like 1 (FSTL1), which serves as a direct activator of Na+,K+-ATPase (NKA). The FSTL1 protein is highly expressed in small-diameter neurons of the dorsal root ganglion (DRG). It is transported to axon terminals via small translucent vesicles and secreted in both spontaneous and depolarization-induced manners. Biochemical assays showed that FSTL1 binds to the α1 subunit of NKA and elevates NKA activity. Extracellular FSTL1 induced membrane hyperpolarization in cultured cells and inhibited afferent synaptic transmission in spinal cord slices by activating NKA. Genetic deletion of FSTL1 in small DRG neurons of mice resulted in enhanced afferent synaptic transmission and sensory hypersensitivity, which could be reduced by intrathecally applied FSTL1 protein. Thus, FSTL1-dependent activation of NKA regulates the threshold of somatic sensation.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 23.08.2022